Parents' Cultural Capital And Its Relationship To Students' Academic Excellence (A Field Study On A Sample Of Students Enrolled In Secondary Schools In Messaad) (مجلة الواحات للبحوث والدراسات, 2025)
The current study aimed to investigate the relationship between parents' cultural capital and students' academic excellence among secondary school students in Messaad. To achieve the study's objectives, we developed a questionnaire addressing the study's variables and distributed it both in paper and electronic formats to a purposive sample of 66 high-achieving secondary school students with an average grade of 14 or higher. The study's findings revealed that the parents' cultural level was moderate. Additionally, a moderate positive correlation was found between parents' cultural capital and students' academic excellence. This relationship did not vary according to gender.Keywords: Cultural, Capital, Academic, Excellence, Parents, Students.